Developing Students’ Professional Communication Skills Based on Linguo-Pragmatic Approach in Teaching Logistics Terminology - Safarova , Dilnavoz Ravshan qizi (The Lingua Spectrum, 2026)
This article examines the theoretical foundations of the linguo-pragmatic approach in teaching logistics terminology in English and its potential for developing professional communication skills. The study analyses the essence of ESP (English for Specific Purposes) methodology and linguo-pragmatic competence, substantiating their role in logistics education. The linguo-pragmatic approach presupposes studying language units from the perspective of communicative situation, social context, and communicative purpose. Works of Hutchinson and Waters, Dudley-Evans and St John, and Basturkmen are reviewed alongside studies by local researchers Muxamedjanova (linguo-pragmatic approach in medical ESP), Urunova (terminology instruction for robotics students), and Botirova (professional communication in logistics education). The article proposes a three-stage theoretical model comprising terminological input, linguo-pragmatic analysis, and communicative production for teaching logistics terminology. The study identifies key linguistic features of logistics terminology – polysemy, widespread use of abbreviations, and multi-word terminological units – and explains why a linguo-pragmatic approach is better suited to teaching them than traditional vocabulary instruction. The article is theoretical in nature and serves as a methodological basis for future empirical research.